Diversity-Oriented Synthesis of Coumarin-Fused Cyclopentanones via a Nucleophilic Phosphine Controlled Cascade Reaction - Huang, Qi; Fu, Junfeng; Chang, Zhixin; Gan, Wenhao; Wang, Yongjiang; Han, Xiaoyu (Synlett, 2022)
A phosphine-promoted intermolecular annulation reaction of functionalized 3-benzoyl coumarin with alkynone has been disclosed. This reaction was found to be highly dependent on the nucleophilicity of the phosphine. Two classes of coumarin-fused cyclopentanones were selectively afforded in moderate to good yields with excellent diastereoselectivities under the mild reaction conditions.
Keywords: diversity-oriented; cyclopentanone; phosphine; annulation